Pemanfaatan Teknologi Informasi, Sistem Manajemen, Transformasi MSDM, Prosedure Pekerjaan dan Kinerja Karyawan - Bayu Imanuddin; IGN Putra Suryanata (Universitas Pendidikan Nasional, 2017)
The purpose of this study was to determine causality Dependent and independent variables. The dependent variable is Utilization Technology, Management Systems, HRM Transformation, Work Procedures and independent variables namely Employee Performance. This study was conducted In Hospitality Project (Study on Bumi Pecatu Graha Badung regency of Bali). The respondents of this study were taken from all employees going projects consist of a population of 340 people with the number of respondents Sampled used as many as 172 people making by Simple Random Sampling. The data were taken using a questionnaire consisted of questions submitted directly to them all to fill. Data were analyzed to test the hypothesis using SEM with AMOS program version 21.0.Based on the analysis of the conclusions drawn that there is a positive effect significantly influence the use of technology on the performance of employees is 0.328, or 32.8%, the effect on employee performance management system amounted to 0,242, or 24.2%, the effect of managementsystems against the working procedures of 0351 or 35 , 1%. Against the influence of HRM transformation work procedures of 0.472, or 47.2%, transformation Effect of HRM on the performance of employees is 0.239, or 23.9%, Influence of working procedures on the performance of employees is 0.271, or 27.1% On Project Hospitality (Study On Bumi Pecatu Graha Badung Regency of Bali).